Use of virtual reality to face didactic obstacles, taking into account the main learning styles. - Flores Cruz, Jesus Alberto (Journal of Learning Styles, 2025)
Self-regulation of learning is linked to better academic results, greater autonomy and motivation in the student. An instrumental study was carried out to design and validate an instrument in the form of a rubric to evaluate teaching practices that promote self-regulation of learning in first, second and third grade students of primary education, through: 1) review of existing instruments to evaluate the self-regulation of learning in students; 2) design of the rubric-type instrument; 3) review and improvement of the instrument by a group of 3 experts; 4) content validation by a group of 15 expert judges in the area; and 5) reliability analysis of the application of the instrument to a pilot group of 24 teachers. In the evaluation by expert judges, all items obtained Aiken V values between 0.71 and 0.91. Cronbach’s alpha is 0.80. It is concluded that the rubric is a relevant instrument for its purpose. Complementary studies of validity and reliability are necessary.